Addatuang Sawitto (1942-1960) - Indira, Fuji; Bosra, Mustari; Najamuddin, Najamuddin (Universitas Negeri Makassar, 2021)
The results show that the role and function of Addatuang Sawitto before independence from 1942 to 1945 was only a symbol because his role in goverment was taken over by Japan. During the reign og the Dutch East Indies, the kings in South Sulawesi, especially in the Kingdom of Sawitto, were subjected to a short agreement or Korte Veklaring. Then during the independence revolution from 1945 to 19429 Addatuang Sawitto said he was submissive and was behind the Republic of Indonesia, but after the Dutch returned to Indonesia with NICA, the power of the aristocrats or kings was returned to the interests of the Netherlands in winning the hearts of the people. Meanwhile, after the independence revolution in 1950 to 1960 after the Dutch recognized Indonesian sovereignty and the elimination of puppet states including NIT and returned to the Republic of Indonesia, the government system was changed, where the system of government of the Kingdom of Sawitto was abolished and replaced by the Pinrang Level II Region. At the time, Addatuang Sawitto had the honor to lead the Pinrang Level II Region by appointing the crown prince or heir to the throne ofÂ the Kingdom of Sawitto. The one who was appointed as regional headwas Andi Makkulawu who was the husband of Addatuang Sawitto We Rukiyah. Thus, the reign of the Kingdom of Sawitto ended and was changed to the Pinrang Level II Region which later became the Pinrang Regency.